Kerajaan Mughal : Puncak Peradaban Islam di Tengah Dominasi Agama Hindu Di India: Penelitian - Annisa Qurratul Aini; Edi Yusrianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Mughal Empire (1526–1858) was one of the largest Islamic dynasties to have existed in India and reached the peak of its glory in the 16th and 17th centuries. Its presence marked an important milestone in the history of Islamic civilization, as it succeeded in flourishing within a predominantly Hindu society. This study aims to describe how the Mughal Dynasty built an advanced Islamic civilization through inclusive political policies, religious tolerance, and harmonious cultural acculturation. The research employed a qualitative method through a literature review that examines the historical, social, cultural, and administrative aspects of the Mughal Empire. The findings reveal that Mughal rulers—particularly Akbar, Jahangir, and Shah Jahan—successfully established political stability by implementing the principle of Sulh-i Kull (universal peace), abolishing religious discrimination, and integrating Hindu elites into the bureaucracy and military. Moreover, Mughal civilization experienced rapid development in the fields of art, architecture, literature, and governmental administration. However, decline began during the reign of Aurangzeb due to stricter religious policies, internal conflicts, military stagnation, and increasing British intervention. This study emphasizes that the Mughal Empire’s success in managing pluralism offers valuable lessons for building multicultural societies in the contemporary world.